Don’t Set Goals, Set Systems: Using Decoding the Disciplines and Students as Partners to Strengthen a History Department and its Teacher Candidates - Jared McBrady (Teaching & Learning Inquiry: The ISSOTL Journal)
This case study presents the development of a system that integrated two strands of SoTL research—Decoding the Disciplines and Students as Partners—into a secondary history teacher preparation program. This system simultaneously refined teaching in undergraduate history courses and provided authentic learning experiences for secondary education teacher candidates. The system involved partnering a teacher preparation course with an undergraduate history course. Teacher candidates interviewed students from that history course to decode bottlenecks in their historical thinking. Teacher candidates then suggested instructional changes faculty could implement to respond to surfaced bottlenecks. This study explores how the connection between Decoding the Disciplines and Students as Partners can address the gap between university instruction and secondary teaching. It further describes how teacher candidates applied the decoding paradigm to analyze learning in undergraduate history courses and proposed curricular improvements. The study reflects on the benefits of this system for stakeholders, including teacher candidates, student researchers, history faculty, and undergraduate students taking history courses. Teacher candidates benefited from the practical experiences of decoding research, including eliciting learning cognition, assessing learner needs, and responding instructionally. Student research partners gained experience in data management and mixed-methods research while providing a valuable perspective as co-analysts. History faculty gained opportunities to have the cognition of their students systematically examined and receive recommendations for improving instruction. Finally, undergraduate students collectively benefited from improved instruction in history courses. This adaptable system could extend beyond history departments into other disciplines, especially in contexts that train secondary teachers.